THE EFFECT OF HORMONE TREATMENT ON DRY SURATI BUFFALO MAMMARY GLAND - H.H. MEHTA,; A.K. PATEL,; K.N. NANDASANA,; U.V. RAMANI,; P.G. KORINGA,; R.G. SHAH,; D. R. BARVALIA,; N.H. KELAWALA,; D.N. RANK,; C.G.JOSHI,; K.M. PANCHAL,; R.K. KOTHARI, (International Journal of Pharma and Bio Sciences, 2013)
Lactation was induced in four non-pregnant, non-lactating buffaloes by subcutaneous injections of estradiol-17β and progesterone for 10 d @ 0.10 and 0.25 mg/kg b. w. /d respectively and Dexamethasone (@ 0.028 mg/kg b.w./d) treatment was given on 17th to 19th d. Milking was initiated on day 20. Biopsies of mammary glands were collected on 0, 7th, 14th, and 21st day from each animal. On 0th day of hormonal treatment on mammary tissues there was abundant connective and adipose tissues with very sparse lobuloalveolar structures. On 7th day, there was decrease in stroma, increase in epithelial cells area with increased lobulo-alveolar architecture. There was accumulation of intra-cellular and intra-luminal secretions with more lipid droplets. From 7th to 21st day, these changes were progressive although variable amongst buffaloes. The average size of the lobule, alveoli as well as number and volume of alveoli were significantly increased on the 21st day as compared to 0 day.